2019
DOI: 10.1002/gcc.22802
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new hypoxia‐regulated epithelial‐mesenchymal transition marker genes labeled by H3K4 acetylation

Abstract: Hypoxia‐induced epithelial‐mesenchymal transition (EMT) involves the interplay between chromatin modifiers histone deacetylase 3 (HDAC3) and WDR5. The histone mark histone 3 lysine 4 acetylation (H3K4Ac) is observed in the promoter regions of various EMT marker genes (eg, CDH1 and VIM). To further define the genome‐wide location of H3K4Ac, a chromatin immunoprecipitation followed by massively parallel DNA sequencing (ChIP‐seq) analysis was performed using a head and neck squamous cell carcinoma (HNSCC) FaDu ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
1
15
0
1
Order By: Relevance
“…Histone 3 lysine 4 acetylation (H3K4Ac) is observed in the promoter regions of EMT marker genes, such as CDH1 and VIM. In hypoxia-induced EMT, HIF-1α induced histone deacetylase and then regulated EMT related gene expression (Wu et al, 2011;Wang et al, 2019). McDonald et al (2011) investigated epigenetic modifications during EMT mediated by TGF-β, they found a reduction in the heterochromatin marker H3 Lys9 dimethylation (H3K9Me2), an increase in the euchromatin marker H3 Lys4 trimethylation (H3K4Me3) and in the transcriptional mark H3 Lys36 trimethylation (H3K36Me3).…”
Section: Histone Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone 3 lysine 4 acetylation (H3K4Ac) is observed in the promoter regions of EMT marker genes, such as CDH1 and VIM. In hypoxia-induced EMT, HIF-1α induced histone deacetylase and then regulated EMT related gene expression (Wu et al, 2011;Wang et al, 2019). McDonald et al (2011) investigated epigenetic modifications during EMT mediated by TGF-β, they found a reduction in the heterochromatin marker H3 Lys9 dimethylation (H3K9Me2), an increase in the euchromatin marker H3 Lys4 trimethylation (H3K4Me3) and in the transcriptional mark H3 Lys36 trimethylation (H3K36Me3).…”
Section: Histone Modificationmentioning
confidence: 99%
“…Bechtel et al, 2010;Carmona et al, 2014;Xiao et al, 2015 Histone modification Histone modifications including acetylation, methylation activate EMT process and fibroblast activation by activation of multiple profibrotic signaling pathways. Pang et al, 2009;Wu et al, 2011;Irifuku et al, 2016;Hewitson et al, 2017;Liu et al, 2019;Wang et al, 2019 microRNAs Several miRNAs are able to regulate multiple transcription factors (i.e., Snail, bHLH, and ZEB), leading to EMT; Some other miRNAs contribute to renal injury by inhibition of EMT process. Davalos et al, 2012;Tang O. et al, 2013;Chen et al, 2015;Díaz-López et al, 2015;Huang et al, 2015 Extracellular vesicles…”
Section: Disturbed Epithelialmesenchymal Crosstalkmentioning
confidence: 99%
“…Because subsequent studies found that H3K4ac is enriched in the promoter regions of genes which associated with cancer-related phenotypic features, such as the estrogen response and the epithelial-mesenchymal transition (EMT) pathway (16,17). In head and neck squamous cell carcinoma (HNSCC) cells, H3K4ac modulated by HDAC3 is enriched around the transcription start site of EMT related genes such like GLI1 and SMO, cooverexpression of which promotes HNSCC cell invasion and migration ability (18). In addition to H3K4ac and H3K9ac, highlevel of H3K23ac, which is correlated with TRIM24, has been observed in patients with HER2-positive breast cancer, and this correlates with a shorter survival interval (19).…”
Section: Imbalanced Histone Acetylation Levels In Tumorigenesismentioning
confidence: 99%
“…Whether the degree of SMO methylation correlates with the tissue specificity remains to be explored. By using a ChIP-sequencing approach, specific histone mark Histone 3 Lysine 4 Acetylation (H3K4Ac) peaks have been confirmed in the proximal promoter of the SMO and GLI1 genes, demonstrating the expression of these genes was regulated by the removal of H3K4Ac mediated by Histone Deacetylase 3 (HDAC3) [ 39 ]. It will be important to perform functional assays to validate transcription factors binding to SMO promoter region and their biological impact using ChIP-seq or site-directed mutagenesis in future studies.…”
Section: Discussionmentioning
confidence: 99%